2019
DOI: 10.1002/chir.23065
|View full text |Cite
|
Sign up to set email alerts
|

Configurational analysis by residual dipolar couplings: A critical assessment of diastereomeric differentiabilities

Abstract: Two independent statistical models for evaluating the certainties of configurational assignments of compounds based on nuclear magnetic resonance (NMR) data are evaluated and compared. Both methods yield weights or probabilities with which two or more structure models (constitutional or configurational isomers or even conformers) could be differentiated based on experimental parameters. Although this paper focusses on the use of residual dipolar couplings (RDCs) for the differentiation of diastereomers, the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 67 publications
1
23
0
1
Order By: Relevance
“…In the absence of a connection between the atomic structure of the alignment medium and the expected RDCs, this comparison is based on a mathematical minimization procedure . Consequently, the utilization of RDCs for structural assignment strongly depends on the number and quality of experimentally observed RDCs, as well as the quality of the structure proposed for the small molecule . The technique, therefore, fails in cases where internuclear vectors are nearly parallel to each other or if they are located in a single plane.…”
Section: Figurementioning
confidence: 99%
“…In the absence of a connection between the atomic structure of the alignment medium and the expected RDCs, this comparison is based on a mathematical minimization procedure . Consequently, the utilization of RDCs for structural assignment strongly depends on the number and quality of experimentally observed RDCs, as well as the quality of the structure proposed for the small molecule . The technique, therefore, fails in cases where internuclear vectors are nearly parallel to each other or if they are located in a single plane.…”
Section: Figurementioning
confidence: 99%
“…The inclusion of additional experimental data is therefore recommended in both cases to resolve or confirm the structural assignment. Immel et al have very recently suggested that relative probability values provided by our current AIC approach are largely overestimated . However, we think that the structural bootstrapping analysis, which includes random modification of structural parameters, performed by the authors throws away important a priori structural information provided by the optimization of the molecular structure.…”
Section: Resultsmentioning
confidence: 99%
“…Standard Monte‐Carlo (MC) based analysis of experimental errors yields distributions of AIC scores for alternate models, which can be used to compute quantitative estimates on diastereomeric differentiabilities [1c,d, 4, 5] . Though this method is used frequently in the literature, we have observed that the back‐calculation of anisotropic NMR data subtly depends on the method from which the structure models were obtained (e.g.…”
Section: Figurementioning
confidence: 99%
“…DFT functional and/or basis sets used). In a recent report we have demonstrated that even for simple molecules such as Isopinocampheol (IPC, 1 ), the inclusion of error estimates on the structure models themselves substantially lowers the certainties of RDC‐based configurational assignments from ≈1:10 −11 to 95 %:5 % [5] . For this, we have been criticized as to introducing “ spurious structural noise ” which “ has to largely undermine discrimination capabilities of the AIC procedure ” [4] .…”
Section: Figurementioning
confidence: 99%